A Report of Eruptive Pruritic Papular Porokeratosis Treated with Abrocitinib - Xia J; Jiang G (Clinical, Cosmetic and Investigational Dermatology, 2023)
Jiali Xia, Guan Jiang Department of Dermatology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, 221002, People’s Republic of ChinaCorrespondence: Guan Jiang, Department of Dermatology, The Affiliated Hospital of Xuzhou Medical University, 99 West Huai Hai Road, Xuzhou, Jiangsu, 221002, People’s Republic of China, Tel +86 181 6877 7336, Email dr.guanjiang@xzhmu.edu.cnAbstract: Eruptive pruritic papular porokeratosis (EPPP) is a subtype of porokeratosis (PK). EPPP is characterized by intense itching and challenging to treat in some cases. Herein, for the first time, a case of successful relief of EPPP treated with abrocitinib was reported. A 75-year-old male with a 60-year history of PK suddenly experienced severe itching in the past 6 months. The patient’s use of antihistamines, prednisone, vitamin A derivatives, vitamin D derivatives, and tripterygium wilfordii showed poor efficacy. Abrocitinib is a highly selective JAK1 inhibitor, and JAK1 appears to play a crucial role in pruritic diseases. Abrocitinib can quickly relieve itching within 24 hours. Before abrocitinib treatment, the visual analog scale (VAS) score was 10, the 12-item pruritus severity scale (12-PSS) score was 19, and the dermatology life quality index (DLQI) score was 18. Abrocitinib (100 mg) was taken orally once a day. After 1 month of oral administration of abrocitinib, the skin lesions gradually subsided, pruritus was relieved, and no adverse side effects occurred. The VAS, 12-PSS, and DLQI scores of the patient decreased to 2, 3, and 4, respectively. This report suggests a potential therapeutic benefit of abrocitinib in managing EPPP. However further investigations with larger sample sizes and controlled studies are necessary to validate its efficacy as a clinical therapy.Keywords: eruptive pruritic papular porokeratosis, porokeratosis, abrocitinib, pruritus, itch, JAK inhibitors